Untargeted Metabolomics of Rind Essential Oils Allowed to Differentiate Two Closely Related Clementine Varieties - González-Mas, María C.; Rambla, Jose L.; Gómez-Cadenas, Aurelio; Blázquez, María Amparo; López-Gresa, María P.; Granell, Antonio (MDPI, 2022)
Chemical characterization of clementine varieties (Citrus clementina Hort. ex Tan.) essential oils (EO) can lead to variety identification and valorization of their potential use in food and aroma industries. The goal of this study was the chemometric discrimination between two very closely related and morphologically identical clementine varieties, Clemenules (NL) and Clemenpons (PO), based on their rind EO, to identify the differential volatile organic compounds (VOCs) and to determine their antioxidant capacity. EO rind volatile profile was determined by gas chromatography coupled to mass spectrometry in Citrus fruit at different ripening stages grown two independent years in two different locations. Untargeted metabolomics and multivariate data analysis showed an evolution of EO volatile profiles markedly parallel in both varieties. Although EO qualitative composition was identical in both varieties, PLS-DA allowed the identification of characteristic VOCs, quantitatively discriminating them along all the ripening process. PO showed higher accumulation of several mono- and sesquiterpene compounds such as trans-carveol, while NL showed higher levels of aldehyde and alcohol non-terpenoids like dodecanal. Both varieties evinced identical EO antioxidant activities, indicating a similar value for food preservation. Hence, untargeted metabolomics approach based on rind EO volatiles was revealed as a powerful technique able to differentiate between morphologically undistinguishable Citrus varieties.